PENGUJIAN HUBUNGAN STRUKTURAL CITRA DESTINASI WISATA, KEPUASAN WISATAWAN DAN LOYALITAS WISATAWAN: KASUS PULAU LOMBOK - Dwi Putra Buana Sakti; Siti Nurmayanti; Hermanto Hermanto (Distribusi - Journal of Management and Business, 2018)
The growing potential of large Moslem tourists has not been fully worked out by Indonesian tourism actors. This opportunity has been anticipated by several neighboring countries by developing seriously halal tourism. Therefore, efforts are needed to develop halal tourism destination in addition to existing public tourism destinations to attract tourists and foreign tourists. The potential of foreign tourists who have not been optimized is a homework that needs to be solved together by tourism stakeholders. This research is intended to examine the structural relationship between the image of Lombok Island as a halal tourist destination, tourist satisfaction and tourist loyalty. The study was conducted in Lombok Island which has been awarded as a halal tourism destination in 2015. Data collection was done through the spreading of questionnaires to 150 tourists who visited the island of Lombok during the period of research conducted. The research findings show the image of Lombok Island as a halal tourism destination affecting the satisfaction and loyalty of tourists who visit it.